Experiments in Teacher Education - Gupta, M. Sen (JOURNAL OF INDIAN EDUCATION, 2012)
Experiments and innovations become worthwhile exercises when these are properly documented so that lessons can be drawn to make the system more effective and responsive to meet the emerging needs. With this in view, an effort has been made in this article to enlist the experimental teacher education programmes undertaken in India such that a long term and informed viewpoint can be developed. This perspective will be useful in professionalising and diversifying the teacher education programme to produce reflective practitioners in the years to come. In the Knowledge Age, the system requires efficient facilitators who can help create intellectually strong, creatively inclined and quality-conscious workforce. The present day teacher training system is the weakest link, mainly because of quantitative expansion and its predominantly theoretical orientation, combined with insufficient duration for value formation. The author has, therefore, presented some innovative ideas worth experimenting based on his experience to make the system rigorous, professional and responsive to the new demands of Knowledge society.